Can physical testing be used to distinguish between migraine and cervicogenic headache sufferers? A protocol for a systematic review - Deborah Falla; Ernesto Anarte; Gabriela Ferreira Carvalho; Annika Schwarz; Kerstin Luedtke (BMJ Open)
Introduction Differential diagnosis of migraine and cervicogenic headache (CGH) can be challenging given the large overlap of symptoms, commonly leading to misdiagnosis and ineffective treatment. In order to strengthen the differential diagnosis of headache, previous studies have evaluated the utility of physical tests to examine for musculoskeletal impairment, mainly in the cervical spine, which could be provoking or triggering headache. However, no systematic review has attempted to evaluate whether physical tests can differentiate CGH from migraine or both conditions from asymptomatic subjects.Methods/analysis A systematic review protocol has been designed and is reported in line with Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols (PRISMA-P). A sensitive topic-based search strategy is planned which will include databases, hand searching of key journals and consultation of relevant leading authors in this field. Terms and keywords will be selected after discussion and agreement. Two independent reviewers will perform the search and select studies according to inclusion and exclusion criteria, including any cohort or observational studies evaluating the topic of this review; a third reviewer will confirm accuracy. A narrative synthesis will be developed for all included studies and, if possible, a meta-analysis will be conducted. The overall quality of the evidence will be assessed using the Quality Assessment of Diagnostic Accuracy Studies (QUADAS-2) checklist for diagnostic accuracy studies and the Downs and Black scale for those studies where the QUADAS-2 checklist cannot be applied.Ethics and dissemination Ethical approval is not required since no patient information will be collected. The results will provide a deeper understanding about the possibility of using physical tests to differentiate cervicogenic headache from migraine and from asymptomatic subjects, which has direct relevance for clinicians managing people with headache. The results will be published in a peer-reviewed journal and presented at scientific conferences.PROSPERO registration number CRD42019135269.